3.3 - x = 3(x - 1.7)
First you simplify the part on the right with the distributive prop.
3.3 - x = 3x - 5.1
Second you add the lowest X, which is - x to both sides
3.3 - x + x = 3x + x - 5.1
3.3 = 4x - 5.1
Then add the 5.1 to make problem easir to solve
3.3 + 5.1 = 4x - 5.1 + 5.1
8.4 = 4x
Then divide.
8.4/4 = 2.1
X = 2.1
2006-12-10 11:03:37
·
answer #1
·
answered by Leilani 2
·
0⤊
0⤋
3.3 - x =3(x - 1.7)
3.3 -x=3x - 5.1
3.3+5.1=3x+x
8.4=4x
8.4/4=x
2.1=x
2006-12-10 19:32:09
·
answer #2
·
answered by Saphira 3
·
0⤊
0⤋
3.3 - x = 3x - 3*1.7
next, get all the x's on one side of the = sign, all terms without x's on the other
3.3 + 5.1 = 3x + x
you should be able to take it from here....
good luck.
2006-12-10 19:02:45
·
answer #3
·
answered by Judy 7
·
0⤊
0⤋
3.3 - x = 3(x - 1.7)
- x = -3.3 + 3( x - 1.7)
- x = -3.3 + 3x - 5.1
- x - 3x = -3.3 - 5.1
- 4x = -8.4
- x = - 2.1
x = 2.1
2006-12-10 19:02:18
·
answer #4
·
answered by Markus D 3
·
0⤊
0⤋
3.3 - x =3(x - 1.7)
3.3 - x = 3x - 5.1
3.3 + 5.1 = 3x + x
8.4 = 4x
x = 2.1
2006-12-10 19:00:21
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
3.3 - x = 3(x - 1.7)
3.3 - x = 3x - 5.1
-3x - x = -5.1 - 3.3
-4x = -8.4
x = -8.4/-4
x = 2.1
check ur answer...
2006-12-10 19:03:15
·
answer #6
·
answered by ifaz 2
·
0⤊
0⤋
3.3 - x =3(x - 1.7)
3.3 - x =3x - 5.1
4x = 8.4
x = 2.1
₢
2006-12-10 19:02:15
·
answer #7
·
answered by Luiz S 7
·
0⤊
0⤋
first get rid of the brackets:
3.3-x = 3x-5.1
then get x to one side (here by adding +x to both sides):
3.3 = 4x-5.1
now let x stand alone on one side (adding +5.1 to both sides):
8.4 = 4x
and finally you get:
2.1 = x
2006-12-10 19:03:34
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
3.3 - x = 3(x-1.7)
3.3 -x = 3x - (1.7)(3)
3.3 - x = 3x -5.1
3.3 -x -3x = -5.1
3.3 -4x = -5.1
-4x = -5.1 -3.3
-4x = -8.4
x = -8.4/-4
x= 2.1
2006-12-10 19:02:22
·
answer #9
·
answered by Karina OV 2
·
0⤊
0⤋
Simplify to 4 x = 8.4
x = 2.1
3.3 -2.1 = 3(2.1 - 1.7)
1.2=1.2
2006-12-10 19:03:08
·
answer #10
·
answered by docrider28 4
·
0⤊
0⤋